2015
DOI: 10.1186/s13073-015-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscapes of tongue carcinoma reveal recurrent mutations in genes of therapeutic and prognostic relevance

Abstract: BackgroundCarcinoma of the oral tongue (OTSCC) is the most common malignancy of the oral cavity, characterized by frequent recurrence and poor survival. The last three decades has witnessed a change in the OTSCC epidemiological profile, with increasing incidence in younger patients, females and never-smokers. Here, we sought to characterize the OTSCC genomic landscape and to determine factors that may delineate the genetic basis of this disease, inform prognosis and identify targets for therapeutic interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 55 publications
12
85
0
Order By: Relevance
“…Fourteen mutations were observed in 7 genes across 12 of 22 samples (Supplementary Table S1). Of note, inactivating NOTCH1 mutation (4%) were found at a lower frequency in our sample set than that reported from the Caucasian population [7, 8, 20] but consistent with similar finding from a recent Asian study [21, 22]. In further contrast to Caucasian population, we observed Notch family receptors, ligands, and downstream effector genes were amplified or over expressed in 59% samples (17 of 29 patients) based on copy number variations called from whole- exome and whole- transcriptome data.…”
Section: Resultssupporting
confidence: 93%
“…Fourteen mutations were observed in 7 genes across 12 of 22 samples (Supplementary Table S1). Of note, inactivating NOTCH1 mutation (4%) were found at a lower frequency in our sample set than that reported from the Caucasian population [7, 8, 20] but consistent with similar finding from a recent Asian study [21, 22]. In further contrast to Caucasian population, we observed Notch family receptors, ligands, and downstream effector genes were amplified or over expressed in 59% samples (17 of 29 patients) based on copy number variations called from whole- exome and whole- transcriptome data.…”
Section: Resultssupporting
confidence: 93%
“…The amplification in this patient's tumor of PIK3CA, CARD11, and SRSF2 and the loss of SMAD2 are mutations that have been reported in other cases of TSCC . Furthermore, amplification of 3q in the region containing the squamous lineage transcription factors TP63 and SOX2, and the oncogene PIK3CA are some of the molecular changes reported in HNSCC which may contribute to the development of the tumor in this patient.…”
Section: Discussionsupporting
confidence: 58%
“…Unfortunately, there are few high‐quality genomic studies investigating early‐onset OSCC to shed light on this issue, and those to date which have focused on tongue SCC have not found much age‐based distinction. A Singaporean study found a tendency towards increased mutations in PIK3CA and MLL2 / KMT2A in late‐onset versus early‐onset OSCC whilst another US‐based study found minimal genomic differences between the two groups …”
Section: Discussionmentioning
confidence: 99%
“…The transformed patients in this cohort were aged above 55 years, although Patient 1 was substantially younger than the overall cohort, having developed OSCC at 40 years of age. This patient is part of a growing cohort of patients developing OSCC at a younger age, earlier than the time the impact of risk factors such as smoking would be expected to manifest. This suggests a potential genetic basis for the propensity of such OPMDs to transform.…”
Section: Discussionmentioning
confidence: 99%